2011
DOI: 10.1182/blood-2010-05-284422
|View full text |Cite
|
Sign up to set email alerts
|

Mutated RAS and constitutively activated Akt delineate distinct oncogenic pathways, which independently contribute to multiple myeloma cell survival

Abstract: We have recently shown that approximately half of primary multiple myeloma (MM) samples display constitutive Akt activity, which disposes them for sensitivity to Akt inhibition. The Akt pathway counts among the signaling conduits for oncogenic RAS and activating mutations of K-and N-RAS frequently occur in MM. We therefore analyzed the relation between RAS mutation and Akt dependency in biopsies and CD138-purified cells from MM patients (n ‫؍‬ 65) and the function of oncogenic RAS for MM cell survival in a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 41 publications
5
71
0
Order By: Relevance
“…9,10 The PI3K/AKT pathway activation in MM is mostly related to signaling from major growth factor receptors such as insulin-like growth factor-1 or interleukin-6. [11][12][13] This dependence on the PI3K/AKT pathway is suggested by the observation that inhibition of the pathway with PI3K inhibitors and/or mTOR inhibitors has been shown to induce apoptosis in myeloma cell lines and in tumor cells derived from patients. 11,14 Afuresertib is a reversible, ATP-competitive, oral, low-nanomolar, pan-AKT kinase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The PI3K/AKT pathway activation in MM is mostly related to signaling from major growth factor receptors such as insulin-like growth factor-1 or interleukin-6. [11][12][13] This dependence on the PI3K/AKT pathway is suggested by the observation that inhibition of the pathway with PI3K inhibitors and/or mTOR inhibitors has been shown to induce apoptosis in myeloma cell lines and in tumor cells derived from patients. 11,14 Afuresertib is a reversible, ATP-competitive, oral, low-nanomolar, pan-AKT kinase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Everolimus exerts its cytotoxic effect by inhibiting the pathway, so that coadministration of everolimus and BI-D1870 can be expected to exert powerful antiproliferative effects on myeloma cells through simultaneous inhibition of both the RAS/ERK1/2 and PI3K/AKT signaling pathways (17). HDACi has shown its antimyeloma effects both in vitro and in vivo, whereas p21 WAF1/CIP1 induction by HDACi has been shown to be one of the mechanisms for HDACi resistance (43)(44)(45).…”
Section: Inhibition Of Rsk2mentioning
confidence: 99%
“…As for myeloma, previous studies have suggested the importance of RSK2 signaling associated with fibroblast growth factor receptor 3 (FGFR3) activation by t(4;14) (13,14). Considering that the activation of RAS/ERK1/2 cascades may occur through various cell-intrinsic molecular abnormalities and extracellular microenvironmental signals regardless of t(4;14) status (15)(16)(17), we hypothesized that RSK2 could be a possible general therapeutic target for multiple myeloma therapy. In this study, we investigated the activation of RSK2, especially of RSK2 Ser227 at NTKD, in myeloma-derived cell lines and patient-derived primary myeloma cells with various cytogenetic abnormalities, and assessed the importance of RSK2 as a potential therapeutic target for multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling of the time-dependent changes in the fluxes of the constituent pathway was performed utilizing modified ordinary differential equation (ODE) and mass action kinetics of proliferation (CDK4-CCND1, CDK2-CCNA, CDK2-CCNE, Creation of cell line models. To create simulation model characterized equivalents of cell lines, the mutation information was derived from resources such as Sanger and other literature research and functionally introduced (Finelli et al, 1999;Ikediobi et al, 2006;Cassinelli et al, 2009;Steinbrunn et al, 2011). The created simulation cell lines models were validated against a set of experimental studies to confirm the definition accuracy (see Table I).…”
Section: In Silico Simulation Of Biological Effectmentioning
confidence: 99%